Rugged bialkali photocathodes encapsulated with graphene and thin metal film - Lei Guo; Fangze Liu; Kazuki Koyama; Nolan Regis; Anna M. Alexander; Gaoxue Wang; Jeffrey DeFazio; James A. Valdez; Anju Poudel; Masahiro Yamamoto; Nathan A. Moody; Yoshifumi Takashima; et al. (Scientific Reports, 2023)
Abstract Protection of free-electron sources has been technically challenging due to lack of materials that transmit electrons while preventing corrosive gas molecules. Two-dimensional materials uniquely possess both of required properties. Here, we report three orders of magnitude increase in active pressure and factor of two enhancement in the lifetime of high quantum efficiency (QE) bialkali photocathodes (cesium potassium antimonide (CsK2Sb)) by encapsulating them in graphene and thin nickel (Ni) film. The photoelectrons were extracted through the graphene protection layer in a reflection mode, and we achieved QE of ~ 0.17% at ~ 3.4 eV, 1/e lifetime of 188 h with average current of 8.6 nA under continuous illumination, and no decrease of QE at the pressure of as high as ~ 1 × 10–3 Pa. In comparison, the QE decreased drastically at 10–6 Pa for bare, non-protected CsK2Sb photocathodes and their 1/e lifetime under continuous illumination was ~ 48 h. We attributed the improvements to the gas impermeability and photoelectron transparency of graphene.